The Influence of Fraud Triangle and Religiosity in Influencing Corruption Intentions in the Village Fund Budget (E-Jurnal Akuntansi, 2026)
Corruption is one type of fraud in Indonesia that must be watched out, because based on international transparency data on January 31 2023, Indonesia's Corruption Perception Index (CPI) in 2022, namely 34, experienced the most drastic decrease of 4 points compared to Indonesia's CPI in 2021. The decreasing score shows that there is a lack of support from stakeholders because it is still slow in responding to corrupt practices. Corruption apparently also occurs in villages, because based on ICW data, since the allocation of village funds by the government in 2015, the trend of corruption cases continues to increase until 2022. The aim of this research is to test and analyze the influence of pressure, opportunity, rationalization and religiosity on intention to commit corruption in the village budget. The research method was carried out quantitatively, by distributing questionnaires to the entire village population in Serang-Banten Regency, totaling 326 villages. The data analysis technique in this research uses SEM-PLS. The results of the study show that (1) Pressure does not influence the intention to corrupt the village fund budget, (2) Opportunity positively influences the intention to corrupt the village fund budget, (3) Rationalization positively influences the intention to corrupt the village fund budget, and (4) Religiosity does not influence the intention corruption in the village fund budget.
Keywords: Village Fund Budget; Pressure; Opportunity; Rasionalization; Religiosity